2004
DOI: 10.1152/ajpendo.00323.2003
|View full text |Cite
|
Sign up to set email alerts
|

Components of a platelet-activating factor-signaling loop are assembled in the ovine endometrium late in the estrous cycle

Abstract: Pulsatile release of uterine prostaglandin F2α (PGF2α) induces luteolysis in ruminants. Exogenous PAF is well known to cause PGF2α release from the ovine uterus. This study examines whether the components of a PAF-signaling loop exist in sheep at the time luteolysis is normally initiated. Day 14 of the cycle was the first day the uterus responded to an infusion of PAF, inducing a significant short-term increase in circulating levels of the PGF2α metabolite. There was a significant increase of PAF concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…Thus, even if relatively constant levels of PAF production occur in the uterus, pulsatile release of PGF2α may occur because of the periodicity of responsiveness of the uterus to PAF. This PAF induced luteolysis hypothesis was confirmed by results published by Chami et al (2004). These authors indicated that the uterus in ewe responded to an infusion of PAF on day 14 of the cycle by increasing the circulating levels of the inactive PGF2α metabolite (PGFM).…”
Section: Implantationsupporting
confidence: 60%
See 2 more Smart Citations
“…Thus, even if relatively constant levels of PAF production occur in the uterus, pulsatile release of PGF2α may occur because of the periodicity of responsiveness of the uterus to PAF. This PAF induced luteolysis hypothesis was confirmed by results published by Chami et al (2004). These authors indicated that the uterus in ewe responded to an infusion of PAF on day 14 of the cycle by increasing the circulating levels of the inactive PGF2α metabolite (PGFM).…”
Section: Implantationsupporting
confidence: 60%
“…(1998) reported that PAF‐R immunoreactivity and mRNA were predominantly detected in human endometrial tissue from the proliferative phase of the menstrual cycle. In ewes, endometrial tissue PAF‐R mRNA expression was significantly induced by estradiol and progesterone in vivo treatment and transcripts were presented between days 10 and 16 of the oestrous cycle (Chami et al 2004). After ovariectomy, PAF concentration in the uterus of rats significantly declined, and this could be restored by treatment with estradiol (Nakayama et al 1991).…”
Section: Implantationmentioning
confidence: 99%
See 1 more Smart Citation
“…The PAF and PAF-R (receptor) synthesis is affected by the presence of steroids in the endometrium in humans (42). Endometrial PAF-R mRNA expression was significantly induced by estradiol and progesterone in sheep (11). After ovariectomy, concentration of PAF in the rat uterus was declined (25).…”
Section: Introductionmentioning
confidence: 99%